Opportunities to better integrate inland fish and fisheries in multilateral environmental agreements - Abigail J. Lynch; Devin Bartley; T. Douglas Beard, Jr.; Gabriel Borba; Steven J. Cooke; Ian G. Cowx; Vittoria Elliott; Holly Embke; Edith Gondwe; Zeb Hogan; Jonathan G. Low; Jamie C. Madden; et al. (Environmental Science & Policy, 2025)

The future of gender research in small‐scale fisheries: Priorities and pathways for advancing gender equity - Emma D. Rice; Edith Gondwe; Abigail E. Bennett; Patrick Asango Okanga; Nimah F. Osho‐Abdulgafar; Kafayat Fakoya; Ayodele Oloko; Sarah Harper; Patrick Chimseu Kawaye; Ernest O. Chuku; Hillary Smith (Fish and Fisheries, 2024)
This paper presents an agenda for the future of gender research in small‐scale fisheries (SSF). Building on expert insight from scholars who gathered during the 4th World Small‐Scale Fisheries Congress Africa (4WSFC) with a synthesis of existing literature, we identify six topics that warrant future investigation in SSF, along with methodological considerations for addressing them. Research priorities include identifying pathways towards (1) equitable participation in governance and decision‐making, (2) valuing all actors' contributions to aquatic food systems, (3) increasing access to financial services, (4) inclusive infrastructural development, (5) livelihood diversification and (6) reducing occupational health hazards. Several important methodological considerations include (i) using multiple methodologies, (ii) applying participatory methods, (iii) collecting gender‐disaggregated data, (iv) integrating gender into a food systems approach in fisheries, (v) engaging an intersectional approach and (vi) operationalising equity.

The ten steps to responsible Inland fisheries in practice: reflections from diverse regional case studies around the globe - Steven J. Cooke; Elizabeth Nyboer; Abigail Bennett; Abigail J. Lynch; Dana M. Infante; Ian G. Cowx; T. Douglas Beard; Devin Bartley; Craig P. Paukert; Andrea J. Reid; Simon Funge-Smith; Edith Gondwe; et al. (Reviews in Fish Biology and Fisheries, 2021)